2019
DOI: 10.3390/biom9070274
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-Derived Small Non-Coding RNAs as Novel Epigenetic Molecules Regulating Adipogenesis

Abstract: tRNA-derived fragments (tRFs), a novel type of non-coding RNA derived from tRNAs, play an important part in governing gene expressions at a post-transcriptional level. To date, the regulatory mechanism of tRFs governing fat deposition and adipogenesis is completely unknown. In this study, high fat diet was employed to induce an obese rat model, and tRFs transcriptome sequencing was conducted to identify differentially expressed tRFs that response to obesity. We found out that tRFGluTTC, which promoted preadipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 27 publications
4
41
0
Order By: Relevance
“…Other studies have highlighted the ability of tsRNAs to regulate stem cell states in murine embryonic stem cells (mESCs), consistent with our ndings [44]. As tsRNAs are a relatively recent area of research, there have been relatively few studies of them to date in vivo [25,[43][44]. As we utilized human bone marrow mesenchymal stem cells as research subjects in our study, further in-vivo validation of our ndings will be challenging.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Other studies have highlighted the ability of tsRNAs to regulate stem cell states in murine embryonic stem cells (mESCs), consistent with our ndings [44]. As tsRNAs are a relatively recent area of research, there have been relatively few studies of them to date in vivo [25,[43][44]. As we utilized human bone marrow mesenchymal stem cells as research subjects in our study, further in-vivo validation of our ndings will be challenging.…”
Section: Discussionsupporting
confidence: 80%
“…tsRNAs have also been shown to play an essential role in the context of cancers, neurological disease, and metabolic disorders [21][22][23][24][25]. In one recent report, researchers found that tRF GluTTC was capable of inhibiting 3T3-L1 preadipocyte differentiation into adipocytes [43]. Interestingly, we identi ed a distinct tsRNA that was able to modulate hMSC adipogenesis, suggesting that these tsRNAs may function via distinct mechanisms in this context.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, it was recently reported that this is not just a consequence of paternal metabolic health, as maternal metabolic effects were also shown to be transmitted across generations via tDRs (44). Maternal metabolic features (e.g., high-fat diet-induced effects) were found to be transferred to F1 offspring sperm (by tDRs), which in turn affected two more generations of offspring (44).…”
Section: Non-mirna Srnasmentioning
confidence: 99%
“…Remarkably, sperm tDRs were reported to not only transmit obesity-associated phenotypes but also alter gene expression in the brains of offspring associated with addiction (44). While these studies and others have reported that sperm tDRs recognize and repress target genes (mRNAs), recent results from Qi Chen and colleagues (45) suggest that RNA base modifications harbored on sperm tDRs conferred the transgenerational metabolic inheritance.…”
Section: Non-mirna Srnasmentioning
confidence: 99%
“…However, in vivo, the effects of KLF11 are less consistent and show either inhibition of proliferation or normal cell growth (Table 2). KLF11 is induced by PPARγ and increases the mitochondrial oxidative capacity Human adipocytes [53] KLF11 is involved in brown adipocyte differentiation and is highly expressed in brown adipose tissue.…”
Section: Klf11 Contributes To the Regulation Of Normal Cell Growthmentioning
confidence: 99%